Pengaruh Penerapan Good Corporate Governance, Kompetensi dan Motivasi Kerja Terhadap Kinerja Keuangan LPD Se-Kecamatan Blahbatuh - Pradnyawati, Ni Kadek Anggi; Hutnaleontina, Putu Nuniek (Hita Akuntansi dan Keuangan, 2024)
This study aims to determine the effect of implementing GCG, competence and work motivation on financial performance. The population in this study were all employees working at the LPD in Blahbatuh District, totaling 186 people consisting of 36 LPDs. The sample in this research is 172 people. The sampling technique is to use the saturated sample method. The analytical method used is multiple linear regression analysis technique. Respondents who were involved in this study included the Chairperson of the LPD, Secretary, Treasurer, Cashier, Head of Funds, Head of Credit, Administration and Savings Collectors. The results of the study show that GCG has a significant positive effect on Financial Performance, Competence has a significant positive effect on Financial Performance, and Work Motivation has no effect on Financial Performance.